2017
DOI: 10.20533/iji.1742.4712.2017.0158
|View full text |Cite
|
Sign up to set email alerts
|

An Option of Hybrid Virtual Labs in an Introductory Biology Course as the Means for Accessible Learning and Enhancing Student Education

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…The authors hypothesized that these students may have struggled due to a lack of time available to devote to classes and proposed ideas such as subsidized on- or near-campus housing and offering additional on-campus jobs to maximize on-campus time for students. Another study has proposed at-home laboratory options as more accessible options for students with significant outside responsibilities.…”
Section: Discussionmentioning
confidence: 99%
“…The authors hypothesized that these students may have struggled due to a lack of time available to devote to classes and proposed ideas such as subsidized on- or near-campus housing and offering additional on-campus jobs to maximize on-campus time for students. Another study has proposed at-home laboratory options as more accessible options for students with significant outside responsibilities.…”
Section: Discussionmentioning
confidence: 99%
“…Rapidly evolving technology, coupled with the COVID-19 pandemic and social isolation measures, have also increased the need for at-home laboratory procedures that effectively teach students chemistry content and laboratory skills . In addition to such recent developments, at-home laboratory experiments better meet the needs of nontraditional students or those who work a significant number of hours, thereby expanding accessibility and promoting equity. , A recently published article found that students who commuted and/or were employed off-campus had lower success rates in introductory college chemistry courses and were less likely to utilize on-campus support services such as recitation sessions. These factors were also correlated with lower socioeconomic status and underserved student populations.…”
Section: Introductionmentioning
confidence: 99%
“…An additional drawback of the above approaches is that they were sometimes not assessed for accuracy, instead focusing on student perceptions. , In some cases, the analyte concentration values were compared to manufacturers’ values, which generally showed reasonable results with average percent errors of 5–20%. Comparisons with manufacturers’ values provides a helpful comparison, but an ideal benchmark for an at-home experiment performed by undergraduates is comparison to typical results of a similar experiment performed in-person. Here, at-home titration (eq ) results are directly compared to the traditional in-person titration (eq ) (sodium hydroxide/phenolphthalein) performed by the same students.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that virtual simulations had positive impacts on students’ retention of skills and broadened their comprehension of fundamental concepts ( 15 ). Data have shown that students perform similarly in introductory biology virtual labs and wet labs, scoring slightly higher in the virtual labs where at-home test-kits were employed, based on analysis of covariance of lab scores comparing F2F lab students with virtual lab students ( 16 ). Students also perceive the accessibility and usefulness of online labs as more convenient and just as effective as wet labs ( 17 ).…”
Section: Introductionmentioning
confidence: 99%
“…Students also perceive the accessibility and usefulness of online labs as more convenient and just as effective as wet labs ( 17 ). Virtual labs are safe, more cost effective, and portable, leading to an increased student preference for this mode of instructional delivery ( 16 , 17 ).…”
Section: Introductionmentioning
confidence: 99%